PENGARUH BUDAYA ORGANISASI TERHADAP MOTIVASI, KEPUASAN KERJA DAN KINERJA KARYAWAN (Studi Pada Perusahaan Pengolahan Kayu Skala Besar di Jawa Timur) - Dr. H. Teman Koesmono, MM (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2006)
The purpose of this research is to find out how big is the effect of organization culture to ward motivation, job satisfaction and employee’s job performance, especially on the employee’s in the production area. The analytical unit is the employee’s in production area sub sector in wood industry in East Java.The research result states that organization culture positively effects motivation, this normal because with organization culture she/ he has someone can reflects her/ his behavior in her/ his working environment. This behavior will be seen in her/ his attitude to the job as the place to fulfill their need and will.The existing phenomenon is that if someone’s behavior is assessed impressive to others or productive to the organization then that can reflects or represent the ability possessed. Individual behavior to ward the organization or their job will be effected by organization culture, this will be found out when the person is doing his/ her job sincerely or not.It is proven in this research that organization culture will be positively effected to someone’s job satisfaction. High performance is everybody’s expectation in the company, but a positive and productive performance will not be achieved if individual behavior is not in the same direction with the company goal. The more positive someone’s behavior will definitely effect her/ his performance, this is proven when the researcher tested the hypothesis that motivation effects the job satisfaction and job satisfaction effects the performance. The result of the direct effect on employee’s motivation toward job satisfaction is 1.659, the direct effect job satisfaction toward job performance is 0.103, the direct effect organization culture toward job performance is 0.127. Besides theoretical findings that were found during the research, the empirical findings were also found: first, the seventh hypothesis states that there are no different employee’s job satisfaction in middle and big companies, P (0.112 ) ≥ α (0.05), therefore the seventh hypothesis cannot be accepted. The second, the eighth hypothesis states that there are different employee’s performance in middle and big companies, P (0.001) ≤ α (0.05), therefore the eighth hypothesis can be accepted.The research result also can give information to Human Resources Manager about the importance of observing and understanding the existing factors in organizational behavior for employees behavior can be directed to the company’s goal in which is established.